Simulation Research On Space-ranging Vector Guidance System Of Tubular Magnetic Sources - Xinyu Dou (Journal of Applied Science and Engineering, 2025)
There is a huge gap between domestic and foreign technology in measurement while drilling (MWD) field, especially in the aspect of MWD of magnetic properties; domestic technology is still lacking in systematic research. Taking the measurement of the magnetic properties of bottom hole assembly (BHA) as the main line, on the one hand, the magnetic field distribution law of built-in BHA magnetic sub in rock stratum is studied; on the other hand, the theoretical research and preliminary design of the magnetic field vector measurement guidance system are carried out for monitoring the space distance between the drilling well and drilled well. Firstly, the three-dimensional space magnetic field law model of tubular magnetic sub of BHA is established by applying the basic theory of the spatial magnetic field law of permanent magnets, and on the basis of this model, the calculation formula of the three-dimensional space magnetic field law of tubular magnetic sub is deduced. Secondly, the magnetic field law of tubular magnetic sub in rock stratum is studied by using the derived formula, and the calculation rules are summarized by combining graphic calculation and numerical calculation. Finally, the calculation rules are applied to calculate separately the adjacent wells distance of the coalbed methane (CBM) connected well and heavy oil double horizontal well, the core algorithm of the magnetic field vector measurement guidance system is obtained, and the calculation rules of the vector distance are verified and analyzed. This method can avoid the complex calculation of permeability and accurately calculate the vector distance between adjacent wells. Meanwhile, this method can be used to guide the research of tubular magnetic sub, magnetic field measurement systems, and the operation of measurement tools.